Early estimates of seasonal influenza vaccine effectiveness in Europe: results from the I-MOVE multicentre case-control study, 2012/13 - Valenciano, M. (2013)
We conducted a test-negative case–control study based in five European sentinel surveillance networks. The early 2012/13 adjusted influenza vaccine effectiveness was 78.2% (95% CI: 18.0 to 94.2) against influenza B, 62.1% (95% CI: −22.9 to 88.3%) against A(H1)pdm09, 41.9 (95% CI: −67.1 to 79.8) against A(H3N2) and 50.4% (95% CI: −20.7 to 79.6) against all influenza types in the target groups for vaccination. Efforts to improve influenza vaccines should continue to better protect those at risk of severe illness or complications.